Excitons in undoped AlGaAs/GaAs wide parabolic quantum wells - Tabata, Américo Sheitiro [UNESP]; Oliveira, José Brás Barreto de [UNESP]; Da Silva, E. C F; Lamas, T. E.; Duarte, C. A.; Gusev, G. M. (IOP Publishing, 2010)
In this work the electronic structure of undoped AlGaAs/GaAs wide parabolic quantum wells (PQWs) with different well widths (1000 and 3000 ) were investigated by means of photoluminescence (PL) measurements. Due to the particular potential shape, the sample structure confines photocreated carriers with almost three-dimensional characteristics. Our data show that depending on the well width thickness it is possible to observe very narrow structures in the PL spectra, which were ascribed to emissions associated to the recombination of confined 1s-excitons of the parabolic potential wells. From our measurements, the exciton binding energies (of a few meV) were estimated. Besides the exciton emission, we have also observed PL emissions associated to electrons in the excited subbands of the PQWs. © 2010 IOP Publishing Ltd.
Keywords: AlGaAs/GaAs; Exciton emission; Exciton-binding energy; Parabolic potential; Parabolic quantum wells; Photoluminescence measurements; PL emission; PL spectra; Sample structure; Sub-bands; Three-dimensional characteristics; Well width; Binding energy; Electronic structure; Excitons; Three dimensional; Semiconductor quantum wells